TIPE NOMINA TAKRIF BAHASA INDONESIA DALAM KARANGAN SISWA SEKOLAH DASAR - Teguh Setiawan (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe definite nominals in the Indonesian language in elementary school students’ writings. The data source was descriptive and narrative writing of elementary school students in Yogyakarta City. The data were analyzed by means of a correspondence method with a referential division and a distribution method with element division, repetition, substitution, and deletion techniques. Based on the data analysis, it can be concluded that definite nominals in the Indonesian language in elementary school students’ writings consist of six types, i.e. (a) personal pronouns, (b) proper nouns, (c) possessive nominal phrases, (d) definite description, (e) demonstrative description, and (f) numeral description. In the realization, definite nominals –except proper nouns and personal pronouns– are not always present with definite markers. Nominals without definite markers can be definite if they are supported by contexts clarifying the referents.